Correlation of Platelet Count with Specific Causative Organism in Culture Positive Sepsis Neonates - An Observational Cohort Study - Tyagaraj, Tanmaya; EV, Nidhi; Subbaiah, Shekar; Yerur, Kishore; Kalkunte, Ramapriya (Archives of Clinical and Biomedical Research, 2024)
Introduction: Thrombocytopenia is one of the frequent hematological issues seen in neonatal sepsis. Thrombocytopenia can be noted in both gram-positive and gram-negative septicemia. Hence it can be considered a predictor for sepsis in neonates. Methods: This study was conducted in Kangaroo Care Women and Children Hospital. Study Design: Retrospective and Prospective Observational Cohort study was conducted. Study Duration: 18 months (January 2022– June 2023). Inclusion Criteria: Neonates admitted to NICU with Culture Positive Sepsis were included in the study. Exclusion Criteria: Neonates with maternal history suggestive of placental insufficiency, low platelet counts, and family history of bleeding disorders. Results: Out of 429 admissions in NICU, 33 neonates had culture-positive sepsis. Among 60.6% of Gram-negative organisms, Acinetobacter baumannii was the commonest seen in 21.2% of neonates. Among 33.3% Gram-positive organisms, coagulase-negative Staphylococcus was the commonest, present in 15.15% neonates. Among 12.1% Fungal Sepsis, all isolated were Candida spp. Few cases had multiple organism infections. Severe thrombocytopenia was seen in 51.51% of neonates, moderate thrombocytopenia in 6.06%, and mild thrombocytopenia in 9.1%. The total mortality was high (33.33%) in septic neonates all cases were with severe thrombocytopenia. The most common organism causing mortality was Candida spp. (27.27%), followed by Klebsiella pneumoniae and Escherichia coli. Conclusions: Mortality was higher in Gram-Negative sepsis. A large percentage of newborns admitted with sepsis had thrombocytopenia. Therefore, thrombocytopenia can be regarded as one of the earliest nonspecific predictors of sepsis in newborns admitted to the NICU. It also greatly affects the outcome.